2018
DOI: 10.1016/j.ins.2018.02.072
|View full text |Cite
|
Sign up to set email alerts
|

A deep dive into user display names across social networks

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain. Highlights  A display name acquisition framework … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…When users register social network accounts, most users will utilize these three features to combine the display name. Li et al [30] concluded that more than 45% of users have the same display name on different social networks, which provides an effective basis for the work of this paper. Accordingly, we used different similarity calculation methods to measure and analyzed the above three features.…”
Section: Display Name Analysismentioning
confidence: 92%
“…When users register social network accounts, most users will utilize these three features to combine the display name. Li et al [30] concluded that more than 45% of users have the same display name on different social networks, which provides an effective basis for the work of this paper. Accordingly, we used different similarity calculation methods to measure and analyzed the above three features.…”
Section: Display Name Analysismentioning
confidence: 92%
“…Li et al [190] 10. user's structural and content information modeling the topics of user's interests from contents, capturing the interest-based and friend-based user cooccurrence in a G to compromise user's privacy.…”
Section: B De-anonymization Methods Employed By the Adversaries To Jmentioning
confidence: 99%
“…After combining the mixed weight, the probability model can be converted into (10). Here, we use a logarithmic formula to avoid the underflow error.…”
Section: P(l|t) ∝ P(l) ×mentioning
confidence: 99%
“…Users can enter their location information manually or automatically via devices. However, for reasons related to protecting personal privacy and security, users are usually reluctant to share their real information [2], [10]. Many users turn off the device's geolocalization function or use forged location information.…”
Section: Introductionmentioning
confidence: 99%